Is It Better to Mobilize Hematopoietic Stem Cells With Pegfilgrastim in Healthy Donors During Allogeneic Hematopoietic Stem Cell Transplantation? - Li, Jiali; Wang, Sanbin; Zhang, Yicheng; Lou, Shifeng; Liu, Yao; Kong, Peiyan; Zhang, Cheng; Gao, Lei; Peng, Xiangui; Wang, Ping; Deng, Xiaojuan; Gao, Li; et al. (Frontiers in Oncology, 2020)
The mobilization of hematopoietic stem cells (HSCs) using granulocyte colony-stimulating factor is a classic method. Recently, a single injection of pegfilgrastim was used to mobilize CD34+ cells in some small-sample studies. To confirm the efficacy and safety of pegfilgrastim in the mobilization of CD34+ cells from healthy donors, we conducted a retrospective multicenter study. A total of 146 healthy donors who all received subcutaneous pegfilgrastim (12 mg) on day 1 were enrolled in our study. Donor HSC apheresis was conducted on day 5. The primary endpoint was the percentage of donors from whom ≥4×106 CD34+ cells/kg were collected in a single apheresis session. The median number of CD34+ cells in donors was significantly higher on day 5 than that on day 4 ((82.26/µL vs. 51.65/µL, P＜0.001). In 111 of the 146 donors, an optimal number of CD34+ cells (≥4×106/kg) were collected in a single apheresis procedure. Bone pain and headache were the main adverse events, but the side effects did not require treatment. The number of white blood cells in most donors dropped to normal levels within one week after apheresis. Nearly 97% of patients achieved neutrophil and platelet engraftment. Pegfilgrastim for mobilization could be used to obtain an optimal number of CD34+ cells in a single session. Pegfilgrastim-induced mobilization not only was effective and safe but also avoided the pain of multiple injections and apheresis procedures in donors. However, prospective randomized controlled trials should be conducted in the future.